Proposta de metodologia para o gerenciamento automático de sistemas fotovoltaicos de geração distribuída - Brandão, Danilo Iglesias [UNESP]; Marafão, Fernando Pinhabel [UNESP]; Farret, Felix Alberto; Simões, Marcelo Godoy (My University, 2013)
The main goal of this paper is to propose a proper methodology for automatic management of a photovoltaic distributed generation system. Such methodology is based on a group of operational premises, as well as energy price in a particular installation and user-driven preferences. Most features of the proposed system are based on the capability of: (i) supplying active and/or reactive power to local loads, (ii) storing energy on a battery bank (iii) selecting loads to be turned on or off; (iv) operating in islanded or connected modes and, (v) acting as active power filter. Finally, some of the proposed operation conditions will be discussed and validated by means of simulation and experimental results.

O objetivo principal deste artigo é propor uma metodologia de gerenciamento automático para um sistema fotovoltaico de geração distribuída. A metodologia apresentada é baseada em um conjunto de premissas de operação, bem como informações relativas ao preço de comercialização da energia em uma dada rede, ou ainda, preferências definidas pelos usuários do sistema. Algumas características do sistema proposto são: (i) capacidade de fornecer energia ativa e/ou reativa para cargas locais e vizinhas; (ii) armazenar energia em um banco de baterias; (iii) priorizar cargas; (iv) atuar conectado ou isolado da rede principal e, (v) operar como filtro ativo de potência. Por fim, algumas das possibilidades de operação do sistema serão discutidas e validadas por meio de resultados de simulação e experimental.
Automatic management methodology for photovoltaic distributed generation systems
Keywords: Active power filter; Automatic energy management; Distributed generation; IEEE 1547; Photovoltaic; Smart grids; Filtro ativo de potência; Fotovoltaico; Geração distribuída; Gerenciamento automático de energia; IEEE 1547; Redes inteligentes de energia